Labor Market Adjustment in Canada and the United States - Thomas, Alun (IMF Working Papers; Working Paper ;, 1997)
This paper provides a quantitative assessment of the relative importance of different labor market adjustment mechanisms in Canada and the United States and also examines the effects of the unemployment insurance (UI) system on labor market adjustment. At the aggregate level, employment growth shocks result in similar unemployment rate responses but smaller wage responses in Canada relative to the United States. Although overall UI generosity has increased aggregate unemployment persistence in Canada, the endogenous component of UI has affected unemployment persistence only marginally. The lower degree of aggregate real wage flexibility in Canada has not been an important determinant of unemployment persistence.